2004
DOI: 10.1097/01.shk.0000132484.97424.32
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I Levels Are a Risk Factor for Mortality and Multiple Organ Failure in Noncardiac Critically Ill Patients and Have an Additive Effect to the Apache Ii Score in Outcome Prediction

Abstract: Cardiac troponin I (cTnI) is a specific marker of myocardial damage used in the diagnosis of acute coronary syndrome (ACS). Recent studies have shown that cTnI levels can also be elevated in patients without ACS, such as in sepsis and trauma patients, and that this is associated with an adverse prognosis. We have evaluated the clinical implications and prognostic significance of serum cTnI levels in noncardiac critically ill patients in a prospective observational study in a general medical intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 44 publications
4
79
1
Order By: Relevance
“…These studies found that ALF patients had subclinical myocardial injury and elevated troponin I levels were associated with a significant increase in the morbidity and mortality. In addition, this phenomenon was observed in certain circumstances, such as acute stroke or sepsis (19,20) and was closely related to the prognosis (21). Therefore, it is speculated that the elevated troponin I is due to subclinical myocardial cell injury, such as necrosis or increased membrane permeability; however, troponin I was not measured in the present patient because the measurement of troponin I was not possible in our hospital.…”
Section: Discussioncontrasting
confidence: 40%
“…These studies found that ALF patients had subclinical myocardial injury and elevated troponin I levels were associated with a significant increase in the morbidity and mortality. In addition, this phenomenon was observed in certain circumstances, such as acute stroke or sepsis (19,20) and was closely related to the prognosis (21). Therefore, it is speculated that the elevated troponin I is due to subclinical myocardial cell injury, such as necrosis or increased membrane permeability; however, troponin I was not measured in the present patient because the measurement of troponin I was not possible in our hospital.…”
Section: Discussioncontrasting
confidence: 40%
“…More recently, data is accumulating that cTnI predicts adverse short-term outcomes irrespective of the clinical setting. For example, the cTnI concentration has been measured in intensive care unit (ICU) patients with noncardiac presentations and was found to be a strong predictor of mortality [18, 19]. However, dialysis patients presenting or referred to an ER differ from patients with a normal renal function, from critically ill ICU patients, or from stable dialysis patients in terms of case mix and acuity, and thus generalizing these findings may not be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…In a study with 108 patients, Wu et al administered invasive ventilation to 53% of the patients, and total mortality was 39%. 7 In a study by Minkin et al, 62% of patients required mechanical ventilation, and total mortality was 39%. 26 In another study, total mortality was 20%, and 34% in pulmonary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Wu et al found that the combination of Tn-I and high Acute Physiology and Chronic Health Evaluation (APACHE II) score was a better risk stratification predictor in ICU patients than was high APACHE II score or elevated Tn-I alone. 7 Therefore, accumulating evidence appears to support the strategy of using multiple biomarkers and assessment instruments in prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation